Current and Emerging Bladder Cancer Urinary Biomarkers - Justin Parker; Philippe E. Spiess (The Scientific World Journal)
Bladder cancer continues to be one of the most common malignancies. Those who have been already diagnosed are at high risk for recurrence, especially if the pathology demonstrates high-grade disease. Diagnosis and surveillance is reliant on invasive evaluation with cystoscopy. Urinary cytology has been used to aid in diagnosis, but its use is limited. Other assays have been developed that may aid in clinical decision making. The ultimate goal will be the development of a highly sensitive and specific urinary marker for bladder cancer. This would provide a noninvasive means of diagnosing the disease and limit the number of unnecessary cystoscopies. This article will review the currently available urinary bladder cancer markers. It will also review new and investigational urinary markers that have shown promise for future clinical use.